2014
DOI: 10.2464/jilm.64.191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seam weld on high temperature deformation behavior in an extruded 6N01 aluminum alloy

Abstract: An aluminum alloy hollow extrusion made with a porthole-die has a few seam welds. It is known that the deformation behavior of a weld region is different from that of a non-weld region at room temperature. In the present study, the influence of a seam weld on the high temperature deformation of a 6N01 aluminum alloy extrusion bar was investigated. The elongation of the alloy with the seam weld was significantly lower than that of the alloy without it. This was because the alloy with the seam weld started local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The direct and overall microstructural investigation on the porthole die extrusion is still lacking. Furthermore, Yasuda's research on the elongation of seam welded aluminum alloy indicates that texture gradient from weld to non-weld region would accelerate the failure of the tensile specimen [5]. Bingöl's experimental results also found striking differences in strength and elongation between tensile specimens at seam weld regions parallel and perpendicular to extrusion directions [27].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The direct and overall microstructural investigation on the porthole die extrusion is still lacking. Furthermore, Yasuda's research on the elongation of seam welded aluminum alloy indicates that texture gradient from weld to non-weld region would accelerate the failure of the tensile specimen [5]. Bingöl's experimental results also found striking differences in strength and elongation between tensile specimens at seam weld regions parallel and perpendicular to extrusion directions [27].…”
Section: Introductionmentioning
confidence: 92%
“…However, the problems arise with the verification of these criteria because welding strength depends not only on the mechanics of the process, but also on its metallurgy, starting from billet casting, homogenization, up to the heat treatment after extrusion. The elongation and the ultimate strength significantly depend on grain size and anisotropy, oxides and inclusion and so on [5,26,27]. Although Edwards [28] and Tang [2] physically simulated welding process to verify FEM prediction, such simulation has its inherent limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alharthi et al (2014) investigated the microstructures of the weld seams of a magnesium alloy using optical microscopy and electron back-scatter diffraction (EBSD). Yasuda et al (2014) analyzed the grain orientations in the weld seam region and found that a difference in recrystallization texture between the weld region and non-weld region would accelerate the start of local necking during mechanical testing.…”
Section: Introductionmentioning
confidence: 99%